Dynamic relationship between board of directors and corporate sustainability performance: evidence from energy sector - Nazir Gardazi, Syeda Saba; Sheikh Hassan, Ahmad Fahmi; Fauzi Saidin, Saidatunur; Johari, Jalila (Penerbit UPM, 2023)
The 2030 agenda for sustainable development establishes a new global sustainability target, with corporations expected to contribute significantly by implementing sustainable practices. One strategy for engaging corporations in sustainable practice focuses on corporate governance (CG) mechanisms, such as the board of directors (BOD). On the premise of stakeholder theory, agency theory and resource dependency theory, the relationship between BOD and corporate sustainability performance (CSP) was investigated using the panel data analysis. Utilising a sample of 335 energy sector corporations from 48 countries our GMM estimation shows a significant relationship between CSP and board size, different positions for CEO and Chairperson roles, and interlocking directors. The findings also showed that having more independent directors on a board lowered CSP, while gender and cultural diversity did not affect CSP. The implications of these findings to policymakers on the energy sector corporations are not limited to improving CSP via formulating and implementing specific CG strategies and policies that are beneficial but also provide explicit information on how corporate energy sectors can change their behaviour with respect to sustainable practices and good governance to address social and environmental issues.